2017
DOI: 10.3389/fpls.2017.01661
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum Inhibits Primary Root Growth by Repressing Auxin Carrier Abundances in Arabidopsis

Abstract: Lanthanum (La) is one of rare earth elements that was used as a crop growth stimulants; however, high concentration of La markedly inhibited plant growth. Our previous study indicated that, although La induced the expression of auxin biosynthesis-related genes, it markedly repressed primary root (PR) elongation by reducing auxin accumulation in PR tips. In this study, we exhibited that La reduces the abundances of auxin carriers. Treatment with La markedly inhibited the auxins IAA-, 2,4-D-, and NAA-induced ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
(54 reference statements)
1
6
0
Order By: Relevance
“…AUX1 plays an important role in the development of the plant root structure as an IAA input vector. Previous studies in this area focused on the change of root configuration. The present study further clarified the role of AUX1 in N absorption, especially under −N conditions. Further, we found that AUX1 regulated RSA (Figure a) in a genotype-dependent manner.…”
Section: Discussionsupporting
confidence: 59%
“…AUX1 plays an important role in the development of the plant root structure as an IAA input vector. Previous studies in this area focused on the change of root configuration. The present study further clarified the role of AUX1 in N absorption, especially under −N conditions. Further, we found that AUX1 regulated RSA (Figure a) in a genotype-dependent manner.…”
Section: Discussionsupporting
confidence: 59%
“…The supplementation of La 3+ with NPA, the auxin transport inhibitor, does not further inhibit the PR growth compared with only the La 3+ treatment. However, the PR growth of the mutants of auxin transport pin1 and pin4-3 are less sensitive, while the gain of function axr3-3/iaa17 is more sensitive, to La 3+ application than WT plants [194] ( Figure 3D and Table S2).…”
Section: Lanthanum (La 3+ ) Toxicitymentioning
confidence: 99%
“…Auxin: La 3+ is a rare-earth metal that inhibits PR growth suppressing auxin transport [194]. La 3+ inhibits the abundance of auxin carriers and reduces auxin accumulation in the PR, by repressing PIN-mediated auxin transport.…”
Section: Lanthanum (La 3+ ) Toxicitymentioning
confidence: 99%
“…1 H NMR (400 MHz, CDCl3) δ 8.54 (ddd, J = 4.9, 1.8, 0.9 Hz, 2H, 6'-Pyr), 7.67 (td, J = 7.6, 1.8 Hz, 3H, 4'-Pyr and CH-Triazole), 7.58 (d, J = 7.8 Hz, 2H, 3'-Pyr), 7.44 -7.33 (m, 5H, Ph), 7.20 -7.15 (m, 2H, 5'-Pyr), 5.53 (s, 2H, CH2-Ph), 3.97 (s, 2H, CH2-Triazole), 3.94 (s, 4H, CH2-Pyr). 13…”
Section: -(1-benzyl-1h-123-triazol-4-yl)-nn-bis(pyridin-2-ylmethyl)me...mentioning
confidence: 99%
“…Lanthanum is dumped in the environment mainly by petrol-producing industries [12], but it can also be dispersed when household equipment is thrown away improperly [12]. As a result, lanthanum gradually accumulates in soil, water, and plants [1,13,14]; moreover, its presence in the marine ecosystem has been shown to be extremely damaging to a variety of aquatic creatures [15].…”
Section: Introductionmentioning
confidence: 99%